Quantification of informal spread of high yielding wheat (Triticum aestivum) seeds among farmers of National Capital Region - SHARMA, NISHI; JOSHI, PRATIBHA; AHMAD, NAFEES; DABAS, J P S; CHAKRAVORTY, S; KUMBHARE, N V; PUNITHA, P; DUBEY, SHANTANU KUMAR; KISHORE, NAND; MAURYA, P P (The Indian Journal of Agricultural Sciences, 2022)
Over decades, the total wheat (Triticum aestivum L.) production of the country has been able to meet the domestic consumption and export considerable amount of it. APEDA reports the export of 2.26 lakh MT of wheat for the worth of `424.94 crores/60.55 USD Millions during 2018–19. Further increase in production is only possible through varietal replacement with varieties having higher productivity potential in the existing production area through horizontal spread. Two reputed wheat varieties of ICAR-IARI, viz. HD 2967 and HD 3086 with good nutrient content and resistance as well as tolerance to major fungal diseases were distributed among 572 farmers of two villages of Haryana and western Uttar Pradesh respectively, with predominant rice-wheat cropping cycle to assess their acceptance level over space and time among villagers through assessment trials from winter (rabi) season 2014–15 to 2019–20. In selected, Haryana and Uttar Pradesh villages the relative yield advantage of HD 2967 was 21.7% and 19.9%, respectively and of HD 3086 was 17.5% and 14.3%, respectively over the local check. HD 3086 additionally reported bold grain, less lodging and less quality loss in the situation of repeated rainfall in maturity stage. The popularity and acceptance of the varieties were evident by the horizontal spread for HD 2967 i.e. 468.2 ha (Haryana) and 383.2 ha (Uttar Pradesh) from 6 and 6.4 ha, respectively from the winter (rabi) season of 2014–15 to 2019–20. The study re-affirms the philosophy of Farmer-to-Farmers spread of modern technologies including the HYV seeds.